2012
DOI: 10.1016/j.jfe.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Certification of family forests: What influences owners’ awareness and participation?

Abstract: a b s t r a c tIn the United States, 35% of the forestland is owned by family forest owners with approximately 0.2% of this land reported to be enrolled in a forest certification system. The current study was conducted to provide insights into factors influencing family forest owners' decisions to certify their lands. The bivariate probit model with sample selection results suggests that receiving professional advice regarding the forestlands and having a written management or stewardship plan had the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
5
2
Order By: Relevance
“…As expected, forest involvement variables were able to explain knowledge, over and above structural variables. Whereas previous studies have revealed links between different types of forest involvement and subjective knowledge (Sun et al 2009;Creamer et al 2012), this study showed that certification and membership in forest owner associations were also associated with higher objective forest knowledge. Most important for both objective and subjective knowledge was involvement in forest planning, although involvement in practical forestry work was not related to any of the knowledge measures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As expected, forest involvement variables were able to explain knowledge, over and above structural variables. Whereas previous studies have revealed links between different types of forest involvement and subjective knowledge (Sun et al 2009;Creamer et al 2012), this study showed that certification and membership in forest owner associations were also associated with higher objective forest knowledge. Most important for both objective and subjective knowledge was involvement in forest planning, although involvement in practical forestry work was not related to any of the knowledge measures.…”
Section: Discussioncontrasting
confidence: 99%
“…By taking forestry courses, communicating with advisors, and interacting with other owners in social networks for example, forest owners are given direct opportunities for learning (Crona and Bodin 2006;André et al 2017). In line with the reasoning that involvement in forest activities will contribute to learning, owners with a management plan and members of a forest owner association have been found to display higher subjective knowledge (Sun et al 2009;Creamer et al 2012). Further, Ingemarson et al (2006 revealed that different owner categories (based on ownership objectives) displayed varying levels of subjective forest knowledge, with passive owners displaying lower subjective knowledge of the forest than multi-objective owners, conservationists, and economists.…”
Section: Learning Environments and Knowledge Among Private Forest Ownersmentioning
confidence: 83%
“…indicated that landowners with forest management plans were likely to manage less forest land for multiple ecosystem services. This result was not consistent with the majority of other studies which reported that possession of a forest management plan was positively related to land allocation for ecosystem services (Creamer et al, 2012, Sullivan et al, 2005, Joshi and Arano, 2009, Gunter et al, 2001. One potential explanation is that landowners who had forest management plans might already have committed their land to other ecosystem services or other outputs such as timber Arano, 2009, Arano et al, 2004).…”
Section: Discussioncontrasting
confidence: 86%
“…Advantages of market access shall also offer sufficient incentives for suppliers to bear the costs of certification [21]. Decisions to participate in certification programmes can be positively influenced by a number of different factors, for example, receiving professional advice or having a written management or stewardship plan [22], market pressure, land-ownership pattern, and water-body abundance [23]. Galati et al [24] argue that influence of internal drivers to adopt voluntary certification linked to a pro-environmental behaviour of owners and managers, such as a signalling mechanism and moral and ethical reasons, is more important than economic or market incentives.…”
Section: Forest Certification and Sustainabilitymentioning
confidence: 99%